Strategic Alliance and Competence Trust: Keys to Successful Marketing Performance in a Yogyakarta Logistics Company - Adipura Danang Maulana; Weni Novandari; Refius Pradipta Setyanto (International Journal of Economics, Business and Innovation Research, 2024)
This study looks at how strategic alliances affect the marketing performance of logistics companies in the Special Region of Yogyakarta. This study places particular emphasis on the mediating role of competence trust. Strategic alliances are important to improve operational efficiency and market access in the era of globalization when the logistics industry is increasingly competitive. It is recognized that trust between alliance partners is an important component that can reduce risk and improve communication, which in turn can result in improved marketing performance. Three hypotheses were made by this study: H1 (strategic alliances impact competence trust), H2 (strategic alliances impact marketing performance), and H3 (strategic alliances impact marketing performance). A quantitative survey with Smart PLS analysis was used, involving 60 companies. The results show that competence trust has a significant influence on marketing performance (H1 accepted), but strategic alliances have no significant influence on competence trust and marketing performance (H2 and H3). The results suggest that trust in alliance relationships is critical to improving marketing performance, and recommend further research involving additional variables.